Em nome de Deus, dos pobres e da libertação: ação pastoral e política em Dom José Maria Pires, de 1966 a 1980 - Pereira, Vanderlan Paulo de Oliveira (2012)
This essay discusses the political activity of Dom José Maria Pires forward from the Diocese of Araçuaí and Archdiocese of Paraíba analyzing their political posturings and his vehement defence of human rights. Although supporting the military coup of 1964, when he was Bishop of that diocese mineira, Dom José has changed its stance about the military regime already in the same year, facing the authoritarianism of the military and defending the victims of the dictatorial regime. Arriving in Paraíba, in 1966, he remained steadfast in the fight against the arbitrariness of the military and sought alternatives to solving problems such as famine and drought, creating two relevant initiatives: the water Drop Operation and the living Church Project. Both concerns are greater than the mere paternalism as present in the ecclesial institution. These initiatives of the Archbishop have evolved in practice marked by radical human rights settlements present in this religious Division. Thus, we highlight two great ranches: Mucatu and Alagamar. In both there was the Human rights violations through the practice of violence, unjust imprisonment, torture and deaths. In Mucatu there were hundreds of people expelled and the destruction of a House that functioned as Office and Church of that community; in Military Police Alagamar, was tortured and terrified peasants. That said, the Bishop denounced these atrocities through sermons, pastoral letters and their presence in these communities. It was in the name of God, the poor and their release policy which the Bishop acted, getting the nickname of Communist and subversive owners and other sectors of society. Throughout the text, also will discuss the political culture and historic culture present in this very charismatic leader.